In-patient multidisciplinary rehabilitation for Parkinson's disease: A randomized controlled trial - Monticone, Marco; Ambrosini, Emilia; Laurini, Alessandro; Rocca, Barbara; Foti, Calogero (Movement disorders, 2015)
Purpose This study was undertaken to evaluate the effects of an inpatient 2‐month multidisciplinary rehabilitative program of task‐oriented exercises, cognitive–behavioral training, and occupational therapy on motor impairment, activities of daily living, and quality of life (QoL) in subjects with long‐duration Parkinson's disease (PD). Methods Subjects were randomly selected for an experimental (multidisciplinary rehabilitative care) and a control group (general physiotherapy) and were assessed before treatment, after 8 weeks (post‐treatment), and 12 months after the end of treatment. Medications were not adjusted during training. Outcome measures were the Movement Disorder Society Unified Parkinson's Disease Rating Scale, Part III (primary outcome), the Berg Balance Scale, the Functional Independence Measure, and the 39‐Parkinson's Disease Questionnaire. A linear mixed model for repeated measures was used for each outcome. Results Seventy subjects with PD (46 females; mean age, 74 ± 7 years; mean disease duration,15 ± 3 years, modified Hoehn & Yahr stage, 2.5‐4) were randomized, 64 completed the study (experimental = 32; control = 32). A significant effect of time, group, and time by group interaction were noted for all outcomes. The primary outcome showed a between‐group difference in favor of the experimental group of 25 points after training, which was maintained at follow‐up. After training, the Berg Balance Scale score of the experimental group was greater than 43.5, a value previously identified as a cutoff between fallers and nonfallers for subjects with PD. Conclusion Our findings suggest that multidisciplinary rehabilitative care is useful in changing the course of motor impairment, balance, activities of daily living, and QoL. The effects lasted for at least 1 y after the intervention. © 2015 International Parkinson and Movement Disorder Society